Steganography in Digital Marketing Using the Least Significant Bit Method - Bayu Charisma Putra; Muhammad Daffa Darmawan; Agung Santoso; Khairil Anam; Dhofirul Yahya; M.Farkhan (Sean Institute, 2026)
Advances in information and communication technology have significantly increased the accessibility of cyberspace, enabling data exchange to occur anytime and anywhere. However, this convenience also increases the risk of unauthorized access and manipulation of confidential information. Therefore, effective data protection mechanisms are required to maintain information security in digital systems. One technique that can be utilized to enhance data protection is steganography, which hides secret messages within digital media so that their existence is not easily detected. This study aims to implement a steganography technique in a digital catalog system to secure product description data by embedding the information within image files. The system was developed as a web-based application using the PHP programming language, while the message hiding process employed the Least Significant Bit (LSB) method on image media in JPG format. The research involved designing and implementing an embedding and extraction mechanism that allows product data to be hidden and retrieved from digital images. The testing results indicate that the system successfully embeds and extracts text messages without causing visible differences between the original image and the stego image, thus fulfilling the fidelity and recovery criteria. However, the embedded data cannot be maintained when the image undergoes manipulation such as cropping, rotation, or contrast modification, indicating that the robustness criterion is not achieved. Overall, the LSB-based steganography approach is effective for concealing product information in digital catalog images, although further development is required to improve resistance to image manipulation.